Práticas integrativas e complementares em saúde nos Centros de Atenção Psicossocial na perspectiva dos profissionais - Thomes, Caroline Rodrigues (2024)
Introduction: The National Anti-Asylum Movement spurred deinstitutionalization in Brazil, solidified by Law 10216/2001, which reorients mental health care and promotes the progressive closure of asylums. In this context, Psychosocial Care Centers have emerged as strategic coordinators of the Psychosocial Care Network, integrating intersectoral resources to promote autonomy and social reintegration. Simultaneously, Integrative and Complementary Health Practices have gained prominence as complementary approaches to conventional therapies. Objective: This study aimed to understand the perspectives of professionals working in Phychosocial Care Centers and municipal managers in Vitória, Espírito Santo, regarding Integrative and Complementary Health Practices. Methods: This is an exploratory, descriptive study with a qualitative approach. The sample was determined by saturation. Semi-structured interviews were conducted with 24 professionals from Psychosocial Care Centers and four managers. The interviews were recorded, transcribed, and analyzed using Bardin´s content analysis. Results: Integrative and Complementary Health Practices are highlighted as promising tools in mental health care whithin Psychosocial Care Centers, fostering comprehensive care, user autonomy, and strengthening therapeutic bonds. Despite structural and operational challenges, their implementation enhances the psychosocial model, contributing to a more humanized Unified Health System in alignment with the principles of the Brazilian Psychiatric Reform. Conclusions: The findings indicate that Integrative and Complementary Health Practices, when integrated into Psychosocial Care Centers, strengthen the psychosocial model and contribute to more comprehensive and humanized care, these practices promote user autonomy and well-being. However, their consolidation within these settings requires joint efforts from managers, professionals, and users to expand their integration into mental health services and reinforce practices centered on comprehensive care and user well-being